2014
DOI: 10.1371/journal.pone.0095018
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Context Influences Micro-Expression Recognition

Abstract: Micro-expressions are often embedded in a flow of expressions including both neutral and other facial expressions. However, it remains unclear whether the types of facial expressions appearing before and after the micro-expression, i.e., the emotional context, influence micro-expression recognition. To address this question, the present study used a modified METT (Micro-Expression Training Tool) paradigm that required participants to recognize the target micro-expressions presented briefly between two identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…These are expressions lasting between 1/25 and 1/5 s. Because of their short time, they may be difficult to capture for an observer and may require advanced video systems . They are also regarded as an expression of the transition between the previous and the current emotion …”
Section: Different Aspects Of Emotional Expressionmentioning
confidence: 99%
“…These are expressions lasting between 1/25 and 1/5 s. Because of their short time, they may be difficult to capture for an observer and may require advanced video systems . They are also regarded as an expression of the transition between the previous and the current emotion …”
Section: Different Aspects Of Emotional Expressionmentioning
confidence: 99%
“…The order of the combination of the model sets and the duration conditions was counterbalanced across participants by balanced Latin square. The micro-expressions were presented by employing the JACBART paradigm ( Matsumoto et al, 2000 ; Matsumoto and Hwang, 2011 ; Shen et al, 2012 ; Zhang et al, 2014 , 2018 ; Svetieva and Frank, 2016 ), in which the expression image (presented for 50, 150, 333, or 450 ms) was sandwiched in between two 1 s presentations of the same expresser’s neutral face (see Figure 2 ). After that, participants were asked to select a single emotion label from a list provided that corresponded to the expression just displayed.…”
Section: Studymentioning
confidence: 99%
“…Only a few studies have investigated this subject. For example, researchers found that, factors like emotional context, duration of facial expressions, age, personality, or profession can affect micro-expression recognition (e.g., Matsumoto et al, 2000 ; Hall and Matsumoto, 2004 ; Hurley, 2012 ; Shen et al, 2012 ; Hurley et al, 2014 ; Zhang et al, 2014 , 2018 ; Shen et al, 2016b ; Svetieva and Frank, 2016 ; Demetrioff et al, 2017 ). Evidence also suggests that there are different EEG/ERPs neural mechanisms underlying the recognition of micro-expressions and macro-expressions (i.e., the typical facial expressions, usually last between 0.5 and 4 s) ( Shen et al, 2016a ).…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to solve this problem, based on the JACBART, Zhang et al ( 2014 ) were the first to explore the role of neutral, sad and happy contexts in the ME recognition task. The results showed that the ACC of recognizing all MEs was decreased in the sad context compared to the neutral and happy contexts, which suggests that participants’ performance in the ME recognition task is influenced by the context.…”
Section: Introductionmentioning
confidence: 99%
“…This study was a further refinement of the JACBART. However, the types of context that were adopted in Zhang et al’s ( 2014 ) study were still limited. Soon after that, Zhang et al ( 2017 ) examined the ME recognition characteristics of college students in fearful, sad, disgusting, angry, surprised and happy contexts.…”
Section: Introductionmentioning
confidence: 99%